2020
DOI: 10.1186/s12879-020-4910-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TNF-α genetic polymorphisms as predictors for sepsis susceptibility and progression

Abstract: Background: The goal of the study was to evaluate a potential role for tumor necrosis factor alpha (TNF-α) genetic variability as biomarker in sepsis. In particular, we aimed to determine if single nucleotide polymorphisms (SNPs) of TNF-α gene are associated with sepsis in terms of risk, severity and outcome. Methods: We performed a prospective study on 163 adult critically ill septic patients (septic shock 65, sepsis 98, further divided in 40 survivors and 123 deceased) and 232 healthy controls. Genotyping of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 77 publications
2
36
0
1
Order By: Relevance
“…This finding supports a prognostic biomarker role for this cytokine. 45 Th17 cytokine production is reduced in sepsis, which may adversely affect long-term mortality. 46 Treatment with IL-7 increases the responsiveness of Th17 cells and reduces the mortality of secondary fungal infections, making IL-17 a potential therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports a prognostic biomarker role for this cytokine. 45 Th17 cytokine production is reduced in sepsis, which may adversely affect long-term mortality. 46 Treatment with IL-7 increases the responsiveness of Th17 cells and reduces the mortality of secondary fungal infections, making IL-17 a potential therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
“…The level of TNF-a was positively correlated with WBC, SAA and IL-6 in the sepsis group, and was positively correlated with IL-6 in the infection group, which also indicated that the level of TNF-α could better re ect the progression of in ammation, and the correlation between TNF-α level and sepsis group was better than that of the infection group. TNF-α plays a central role in systemic in ammatory response due to its ability to release other cytokines in the early stage of infectious disease and its direct in uence in septic shock, and plasma levels of TNF-α are associated with sepsis induced death [32]. The level of PCT was positively correlated with IL-6 only in the sepsis group and CRP only in the infection group.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG analysis has identified the TNF signaling pathway as the top one significantly enriched pathway from DEGs that were upregulated in LPS-treated group while suppressed in the DY131-treated group. TNF-α is the key inflammatory factor involved in the progression of sepsis (Ertel et al, 1994;Georgescu et al, 2020;Parameswaran and Patial, 2010;Spinas et al, 1992). In clinical research, TNF-α was considered as the initial factor that triggered and mediated the sepsis (Parameswaran and Patial, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical research, TNF-α was considered as the initial factor that triggered and mediated the sepsis (Parameswaran and Patial, 2010). TNF-α level was dramatically increased in the serum from patients with multiple causes-induced septic shock, and was positively correlated with disease severity and prognosis (Georgescu et al, 2020). Thus, TNF-α and its related signaling pathways are important targets for the treatment of sepsis.…”
Section: Discussionmentioning
confidence: 99%